COVID-19 in the Central Nervous System - clinical manifestations and post-COVID syndrome - an update - Śmigiel, Aleksandra; Mularczyk, Zuzanna; Oleksy, Piotr; Reclik, Magdalena; Góralczyk, Ewa; Rzepka, Michalina; Siuda, Joanna (Journal of Education, Health and Sport, 2024)
Introduction: The COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), represents a significant global public health challenge. While respiratory symptoms dominate, the virus's impact on other systems, particularly the central nervous system (CNS), has gained increasing attention. SARS-CoV-2 demonstrates tropism for Angiotensin-Converting Enzyme 2 (ACE2) receptors, expressed in the olfactory epithelium, lungs, endothelium, kidneys, enterocytes, and neurons, contributing to neurological manifestations observed during the acute phase of the disease. Materials and Methods: A literature review was conducted using PubMed, Scopus, Web of Science, and ScienceDirect databases. Keywords included: COVID-19, Post Acute COVID-19 Syndrome, SARS-CoV-2 Virus, Neurological Manifestations, and Central Nervous System Viral Diseases. A total of 58 articles were selected for analysis based on relevance and quality of evidence regarding neurological symptoms and complications associated with COVID-19. Basic Results: The acute phase of COVID-19 frequently involves neurological symptoms such as frontal and holocranial headaches, dizziness, gustatory and olfactory dysfunctions, and alterations in consciousness. Severe complications, though less common, include encephalitis, ischemic and hemorrhagic stroke, cerebral venous thrombosis, and myelitis. These conditions often present as altered mental status, seizures, aphasia, headaches, or focal deficits, contributing substantially to patient morbidity and mortality. Conclusions: Neurological symptoms and complications constitute a significant aspect of COVID-19, highlighting the virus's potential to affect the CNS. While severe complications are rare, their profound impact on prognosis underscores the importance of early recognition and management. Further research is essential to understand the pathophysiology and optimise therapeutic approaches for affected patients.